(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
The lack of professional medical staff was vigorously felt in 19th century Ottoman Macedonia. Aside from the Turkish military medics in the local garrisons, only a negligible number of Christian doctors could be found in Macedonian cities. Finding a doctor in the countryside was another rare occurrence. These circumstances placed the doctors in the highest levels of the social pyramid. The foreign diplomats and clerics were aware of the perspectives which would open up if they succeeded in their attempts to provide patronage over the medical staff in Ottoman Macedonia. Therefore, in the last decade of the 19th century, the Ministries offoreign affairs of the Balkan states spared no resources to finance their own medical phalanx in Macedonia. The first victim in this struggle for followers was the Macedonian Christian population, which, in order to satisfy its basic human and medical needs, was forced to make compromises with itself and its national consciousness. Here we are taking a look into the manners in which the Bulgarian propaganda and the propaganda of the other Balkan countries used the medics in order to exercise their conquering plans in Macedonia. Thereby, we will use comparative analysis to test the thesis of the Bulgarian historiography, according to which the Greek, Serbian and Romanian doctors in Ottoman Macedonia were propagandists, while the activities of the Bulgarian medics were “purely humanitarian, and aimed at healing the Bulgarian population ”.